Endocannabinoid system involvement in drug addiction, depression, and neurotic disorders - Vršková, Dagmar (Scripta medica Facultatis medicae Universitatis Brunensis Masarykianae, 2008)
The aim of this paper is to bring to attention recent evidence on the roles of the central endocannabinoid system in neuropsychopathological conditions such as drug dependence, depression, anxiety, and aggression. Results of pharmacological studies with cannabinoid receptor ligands in rodent behavioural models reported (behavioural sensitisation to drugs of abuse – “open-field test”, “agonistic behaviour”, “I.V. drug self-administration”; depression – “bilateral olfactory bulbectomy”, “repeated social defeat”; aggressiveness, and anxiety – “agonistic behaviour”) are expected to show in their outcomes a possibility of predicting therapeutic pharmacological intervention into the endocannabinoid system activity in the above-mentioned neuropsychiatric disorders.
Keywords: Models, Animal; neurotické poruchy; myši; Cannabinoid Receptor Modulators; úzkostné poruchy; modely u zvířat; deprese; Substance-Related Disorders; Mice; poruchy spojené s užíváním psychoaktivních látek; Receptors, Cannabinoid; Cannabis; Depression; Neurotic Disorders; Anxiety Disorders; receptory kanabinoidní; modulátory kanabinoidních receptorů